2017
DOI: 10.1097/md.0000000000008897
|View full text |Cite
|
Sign up to set email alerts
|

Altered effective connectivity of resting state networks by acupuncture stimulation in stroke patients with left hemiplegia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…In our previous studies [46][47][48][49][50], we gradually and deeply proved that compared with healthy subjects, acupuncture at Yanglingquan(GB34) in patients with hemiplegia showed speci c activation of brain regions and expressed bilateral effects, from the perspectives of single spot, single network and compound network, which provides a relatively deep research foundation for the hypothesis of bilateral cerebral coordinated regulation in this study. For the purposes of task control and reducing the confounding factors of intervention, single acupoint is selected in this study, which is not the actual clinical practice.…”
Section: Discussionmentioning
confidence: 70%
“…In our previous studies [46][47][48][49][50], we gradually and deeply proved that compared with healthy subjects, acupuncture at Yanglingquan(GB34) in patients with hemiplegia showed speci c activation of brain regions and expressed bilateral effects, from the perspectives of single spot, single network and compound network, which provides a relatively deep research foundation for the hypothesis of bilateral cerebral coordinated regulation in this study. For the purposes of task control and reducing the confounding factors of intervention, single acupoint is selected in this study, which is not the actual clinical practice.…”
Section: Discussionmentioning
confidence: 70%
“…According to the results of previous studies [ 32 ], acupuncture is beneficial for motor function recovery in stroke patients with hemiplegia and is considered to be safe [ 33 , 34 ]. The mechanism of motor recovery due to acupuncture in stroke hemiplegia may be related to brain plasticity [ 35 ]. Acupuncture in one limb can stimulate bilateral brain areas, increase cerebral blood flow and regulate motor areas damaged by stroke [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture in one limb can stimulate bilateral brain areas, increase cerebral blood flow and regulate motor areas damaged by stroke [ 36 ]. For example, acupuncture in yanglingquan can regulate multiple brain networks in stroke patients [ 35 ]. Thus, it promotes the recovery of hemiplegia limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study on the effects of sample size on cerebral response to acupuncture with fMRI had shown that the imaging results in 17 healthy controls were similar to the results of studies with 21 cases [ 34 ], which may suggest that approximately 20 subjects maybe a relatively common choice in rs-fMRI studies after acupuncture. The sample size in acupuncture mechanism study using rs-fMRI with stroke patients typically ranges from a few cases to approximately 20 cases [ 33 , 35 37 ]. Because this trial is a neuroimaging study, the primary outcome will be based on the subjects' MRI image processing, and patients with left cerebral ischemia accompanied by right limb hemiplegia will be enrolled in this study so as to ensure the relative consistency of cerebral ischemia lesions and reveal the neuroimaging mechanism more regularly.…”
Section: Methodsmentioning
confidence: 99%